2021
DOI: 10.14348/molcells.2021.0045
|View full text |Cite
|
Sign up to set email alerts
|

Inositol Polyphosphate Multikinase Signaling: Multifaceted Functions in Health and Disease

Abstract: Inositol phosphates are water-soluble intracellular signaling molecules found in eukaryotes from yeasts to mammals, which are synthesized by a complex network of enzymes including inositol phosphate kinases. Among these, inositol polyphosphate multikinase (IPMK) is a promiscuous enzyme with broad substrate specificity, which phosphorylates multiple inositol phosphates, as well as phosphatidylinositol 4,5-bisphosphate. In addition to its catalytic actions, IPMK is known to non-catalytically control major signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Finally, we transfected cells with two different siRNAs targeting inositol polyphosphate multikinase (IPMK), an upstream kinase required for both IP 5 and IP 6 biosynthesis 28 , 29 . We assessed Integrator function using two reporters where the U7snRNA promoter, gene body, and 3′ cleavage site are placed upstream of either GFP or luciferase with the rationale that loss of Integrator function leads to transcriptional readthrough and expression of the downstream open reading frames (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we transfected cells with two different siRNAs targeting inositol polyphosphate multikinase (IPMK), an upstream kinase required for both IP 5 and IP 6 biosynthesis 28 , 29 . We assessed Integrator function using two reporters where the U7snRNA promoter, gene body, and 3′ cleavage site are placed upstream of either GFP or luciferase with the rationale that loss of Integrator function leads to transcriptional readthrough and expression of the downstream open reading frames (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…IP3 can be subsequently phosphorylated by inositol kinases yielding several phosphorylated species (e.g. inositol 1,4,5,6 tetrakisphosphate (IP4), inositol 1,3,4,5,6 pentakisphosphate (IP5), inositol 1,2,3,4,5,6 hexakisphosphate (IP6), and 5-diphosphoinositol pentakisphosphate (IP7)) [ 78 , 79 ]. The second cellular source of inositol polyphosphates (IPs) is hydrolysis of membrane phospholipids—a process tightly involved in cellular signal transduction, where IPs act as messenger molecules mediating various processes.…”
Section: Chromatin-regulating Metabolites Originating From Carbohydratesmentioning
confidence: 99%
“…The soluble inositol poly/pyro-phosphates are involved in many different cellular systems (reviewed by [ 76 , 77 ]). Wu et al showed that Sse1, Hsp26, Ssb1/2 and Hsp104, among many other proteins, bound to affinity columns prepared with 5PP-IP5 or IP6 [ 78 ].…”
Section: Siw14 Curing Of [Psi+] and Inositol Polyphosphatesmentioning
confidence: 99%